1990
DOI: 10.1113/jphysiol.1990.sp018119
|View full text |Cite
|
Sign up to set email alerts
|

Chloride‐sensitive nature of the adrenaline‐induced current in guinea‐pig cardiac myocytes.

Abstract: SUMMARY1. Ionic selectivity of an adrenaline-induced current was investigated in single guinea-pig ventricular cells by recording whole-cell currents using the patch clamp technique combined with internal perfusion. Other ionic currents and exchange currents known in ventricular cells were suppressed by appropriate inhibitors and the adrenaline-induced current was defined as a difference between currents obtained in the presence and absence of adrenaline.2. The adrenaline-induced current was time independent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
77
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(98 citation statements)
references
References 31 publications
20
77
1
Order By: Relevance
“…Secondly, the holding potential is concerned with the (Bahinski et al, 1989;Harvey & Hume, 1989;Matuoka et al, 1990). The reversal potential for this current depends on the external and internal Cl-concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the holding potential is concerned with the (Bahinski et al, 1989;Harvey & Hume, 1989;Matuoka et al, 1990). The reversal potential for this current depends on the external and internal Cl-concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Using the model of the oil gap, composed of the membrane capacitance and resistance distributed along the cell axis in both the oil gap and the external compartment (cable theory: Cole & Curtis, 1938;Hodgkin & Rushton, 1946; see also Ishihara et al 1989), the resistance of the water layer around the cell within the oil gap was calculated. If a membrane conductance of 25 pS/pF was used, which is that found in the absence of the inward rectifier K+ current (Matsuoka, Ehara & Noma, 1990), a total membrane conductance of 1000-1250 pS was obtained, which gives a resistance of 0-8-1-0 GQ. An intracellular axial resistance of 104 MQ/cm was assumed.…”
Section: Voltage Clamp Experimentsmentioning
confidence: 99%
“…In the myocardium, ~-adrenergic agonists regulate a variety of ionic currents (for reviews, see Hartzell, 1988;Gadsby, 1990), including a CI-current identified recently in guinea pig and rabbit ventricular myocytes (Harvey and Hume, 1989;Bahinski, Nairn, Greengard, and Gadsby, 1989b;Matsuoka, Ehara, and Noma, 1990). Activation of that CI-conductance requires phosphorylation by cAMP-dependent protein kinase (PKA) because the CI-conductance can be elicited by direct intracellular application of either cAMP or the catalytic subunit of PKA (Bahinski et al, 1989b), and it can be abolished (Bahinski, Gadsby, Greengard, and Nairn, 1989a;Hwang, Horie, Nairn, and Gadsby, 1992c) by intracellular application of a specific peptide inhibitor of PKA (PKI; i.e., Walsh inhibitor, 5-24-amide; Cheng, Kemp, Pearson, Smith, Misconi, Van Patten, and Walsh, 1986).…”
Section: Introductionmentioning
confidence: 99%